The Expression of the Pronominal Subject in the Spoken Spanish of the Colombian Caribbean - Perez Cordoba, Alder Luis [UNESP]; Camacho, Roberto [UNESP] (Univ Pedagogica & Tecnologica Colombia, 2021)
This paper aims to analyze the sociolinguistic conditioning factors that motivate the expression of the pronominal subject in the Spanish spoken in the Colombian Caribbean. The sample consisted of recordings of 18 informants for each sociolinguistic corpus (Barranquilla, Cartagena and Valledupar), which make up the variety spoken in the Colombian Caribbean, collected based on the PRESEEA methodology. The cases were adapted to the coding guide for the expression variable of the pronominal subject of the PRESEEA. The quantitative analysis was carried out with the Rbrul program. The similarity observed in a preliminary contrastive study of the varieties and the exclusion of the subdialect predictor reveal the coherence of the dialect in terms of pronominal expression. The results show a high rate of pronominal expression (44.2%) for the analyzed variety, which includes it among the Caribbean ones. The multivariate analysis showed that nine linguistic and two social variables play a significant role in pronominal variation and confirm the strong and complex influence of linguistic factors, much more than social, on the variable.
Keywords: pronominal subject; Caribbean Spanish; Colombia; PRESEEA; variationist sociolinguistics